Adipose Tissue-Derived Microvascular Fragments From Male and Female Fat Donors Exhibit a Comparable Vascularization Capacity - Später, Thomas; Marschall, Julia E.; Brücker, Lea K.; Nickels, Ruth M.; Metzger, Wolfgang; Mai, Ann-Sophie; Menger, Michael D.; Laschke, Matthias W. (Frontiers in Bioengineering and Biotechnology, 2021)
Adipose tissue-derived microvascular fragments (MVF) represent effective vascularization units for tissue engineering. Most experimental studies exclusively use epididymal fat tissue of male donor mice as a source for MVF isolation. However, in future clinical practice, MVF-based approaches may be applied in both male and female patients. Therefore, we herein compared the vascularization capacity of MVF isolated from the epididymal and peri-ovarian fat tissue of male and female donor mice. Freshly isolated MVF from male and female donors did not differ in their number, length distribution, viability and cellular composition. After their assembly into spheroids, they also exhibited a comparable in vitro sprouting activity. Moreover, they could be seeded onto collagen-glycosaminoglycan matrices, which were implanted into full-thickness skin defects within mouse dorsal skinfold chambers. Repetitive intravital fluorescence microscopy as well as histological and immunohistochemical analyses revealed a comparable vascularization and incorporation of implants seeded with MVF of male and female origin. Taken together, these findings demonstrate that the vascularization capacity of MVF is not gender-specific.